Older adults’ trajectories through the criminal justice system: a brief report from a nominal group - Heathcote, Leanne (The journal of forensic psychiatry & psychology, 2025)
The number of older people in prison and entering the Criminal Justice System (CJS) is increasing. This population often presents with complex needs which can be underserved. This paper aims to explore staff experiences of supporting older prisoners across the CJS, from police custody, through courts, into prison, and release from prison, identifying existing forms of care provision, challenges, and areas for improvement. To accomplish this, 13 professionals were recruited to a nominal group discussion, including a general practitioner, an older adult clinical psychologist, social worker, a prison governor, prison healthcare manager, probation officer, Health & Justice Lead, older adult nurse, as well as third sector and supported housing representatives. Seven key themes were identified: 1) ‘pre-prison pathways’; 2) ‘secure nursing homes’; 3) ‘prison custody environment’; 4) ‘flexible regimes’; 5) ‘specialised health and social care’; 6) ‘a spectrum of need’; and 7) ‘release of older adults from prison custody’. Within the group, there was consensus that the processes and environments in place across the CJS were unsuitable for older prisoners. Several areas for improvement were identified to develop more equitable and suitable routes for older adults in the CJS.